Review of Designing the search experience: the information architecture of discovery - (:unkn) unknown (My University, 2013)
In the book Designing the Search Experience: The Information Architecture of Discovery, Tony Russell-Rose and Tyler Tate question the search for information on the web and in other environments.
Keywords: information architecture